The Views of William Muir in the Belief of Qur’anic Sources from the Bible: A Critical Evaluation - Aliyu Kabir; Mohammed Muneer’deen Olodo Al-Shafi’i (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract One of the earliest claims made by medieval Christian missionaries is that the Prophet Muhammad (saw) derived the Glorious Qur’Én from the Judeo-Christian tradition, even the most learned among them agreed with this idea, and believed it to be true. This assertion was also supported by Muir while discussing the sources of the Glorious Qur’Én. Although this claim is debatable, it needs to be supported by accurate, concrete and convincing evidence, but Muir lacked this and instead relied on some weak evidences. The aim of this paper is to examine, analyze, and evaluate Muir’s views regarding the sources of the Glorious Qur’Én in the light of Islamic perspectives and historical fact. This study will be conducted using qualitative method, specifically in a library-based setting. According on the findings of investigation, the idea that the Glorious Qur’Én comes from Judeo-Christian sources can in no way be considered reasonable or true. This is due to the fact that upon closer examination, many channels through which, as Muir suggested, the Prophet (saw) encountered the Jewish and Christian traditions, lack sufficient evidence to support their authenticity. In fact, they have been proven wrong in every conceivable perspective. اﻟﻤﻠﺨﺺ: من أقدم ادعاءات المبشرين المسيحيين في العصور الوسطى هو أن النبي محمد (ص) اشتق القرآن الكريم من التقاليد اليهودية المسيحية، وحتى أكثرهم علًما وافقوا على هذه الفكرة واعتقدوا بصحتها. وقد أيد موير أي ًضا هذا التأكيد أثناء مناقشته لمصادر القرآن الكريم. ويدل جميع ادعاء موير هذا على أنه لم ينظر إلى القرآن كوحي إلهي منّزل ح ّق، حيث أنه أخذه بشكل كامل مجموعة نبويًة مستمًدة من مصادر إنجيلية عديدة ومتنوعة. على الرغم من أن هذا الادعاء قابل للنقاش، إلا أنه يحتاج إلى دعم بأدلة دقيقة وملموسة ومقنعة، ولكن موير افتقد ذلك واعتمد بدله على بعض أدلة ضعيفة. وفي نهاية المطاف، فإن الفكرة بأن القرآن الكريم جاء من مصادر يهودية ومسيحية لا يمكن اعتبارها معقولة أو صحيحة بأي حال من الأحوال. ويرجع ذلك إلى أنه، عند الفحص الدقيق، فإن العديد من القنوات التي التقى من خلالها النبي صلى الله عليه وسلم بالتقاليد اليهودية والمسيحية، كما اقترح موير لدعم صحتها، تفتقد أدلةكافية. و فقد ثبت في الواقع خطأهم في كل وجه من الأوجه.